2009
DOI: 10.1111/j.1471-4159.2009.05991.x
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic expression of human equilibrative nucleoside transporter 1 in mouse neurons

Abstract: Transgenic mice that express human equilibrative nucleoside transporter subtype 1 (hENT1) under the control of a neuron‐specific enolase promoter have been generated. Southern blot and PCR revealed the presence of the transgene in five founder mice. Mice from each founder line were examined by reverse transcriptase (RT)‐PCR and found to express hENT1 in RNA isolated from whole brain, cerebral cortex, striatum, hippocampus, and cerebellum but not liver, kidney, heart, lung or skeletal muscle. Cortical synaptoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 35 publications
2
38
0
Order By: Relevance
“…Here we have used a molecular approach based on quantitative real-time RT-PCR, and our findings correlate with previous studies (7,8,17). Moreover, description of an ENT1 overexpressing transgenic model reported no compensatory effects in the expression of adenosine receptors, other nucleoside transporter isoforms, or purine metabolizing enzymes (38).…”
Section: Discussionsupporting
confidence: 83%
“…Here we have used a molecular approach based on quantitative real-time RT-PCR, and our findings correlate with previous studies (7,8,17). Moreover, description of an ENT1 overexpressing transgenic model reported no compensatory effects in the expression of adenosine receptors, other nucleoside transporter isoforms, or purine metabolizing enzymes (38).…”
Section: Discussionsupporting
confidence: 83%
“…68 On the other hand, transgenic overexpression of human ENT1 in mouse neurons increases sensitivity to the acute intoxicating effects of alcohol. 69 In summary, the ENT1-dependent increase in the extracellular concentration of adenosine, by acting on A 1 receptors localized in different brain areas, seems to play a very important role in the ataxic, somnogenic, and anxiolytic effects of the acute administration of alcohol. Does adenosine also play any role in the reinforcing effects of alcohol?…”
Section: Ferré and O'brienmentioning
confidence: 99%
“…In fact, chronic alcohol exposure results in a decreased expression of ENT1 and, therefore, a decrease in alcohol-mediated inhibition of ENT1. 69 The loss of reuptake of adenosine after chronic exposure to alcohol is most probably the main mechanism by which alcohol tolerance develops both in cell lines 69 and animals. 72 Several studies have shown that the consequent reduction in the adenosine tone is associated with an upregulation of A 1 receptors, which seems to be at least partially responsible for the tolerance to the acute effects of alcohol and also to the main symptoms of alcohol withdrawal, such as insomnia, anxiety, and seizures (Fig.…”
Section: Adenosine Mechanisms In the Chronic Pharmacological Effects mentioning
confidence: 99%
“…Given that during excitotoxic conditions, adenosine appears to be released selectively from neurons via a nucleoside transporter mechanism, we developed a transgenic mouse model to further explore adenosine release mechanisms [23] . A transgene consisting of the rat promoter region for neuron specific enolase was coupled to the coding sequence of human equilibrative nucleoside transporter 1 (hENT1) and used to develop mice with neuron specific expression of hENT1.…”
Section: Cultured Neurons But Not Astrocytes Release Adenosine Via mentioning
confidence: 99%
“…We reasoned that ENT facilitate adenosine efflux during events where adenosine receptor mediated effects are a result of intracellular adenosine formation, subsequent to ATP utilization, yet facilitate adenosine influx during events where adenosine receptor mediated effects are a result of extracellular adenosine formation ( Figure 2). Since neurons are more sensitive to ischemic injury than astrocytes and show more rapid depletion of intracellular ATP [20] , and since in cell culture rat neurons appear to release adenosine per se during stroke-like conditions [22] , we created mice with neuron specific expression of hENT1 [23] .…”
Section: Cultured Neurons But Not Astrocytes Release Adenosine Via mentioning
confidence: 99%